Detection of Mycoplasma gallisepticum and Mycoplasma synoviae antigens by immunohistochemical method in pneumonic broiler chicken lungs - Yilmaz, Fethi; Timurkaan, Necati (My University, 2011)
The purpose of this study was to detect Mycoplasma gallisepticum (MG) and Mycoplasma synoviae (MS) antigens by immunohistochemical method in pneumonic broiler chicken lungs. The material of the study was composed of paraffin blocks of lungs taken from 275 pneumonic chickens. The cross-sections which were taken to paraffin blocks were stained with Avdin Biotin Complex (ABC) technique. MG antigens in 7, MS antigens in 11 samples were determined out of 275 pneumonic chicken lungs. It was found that E. coli and Proteous sp. in 6 cases were identified in 11 positive MS cases and ii. coli were identified in 3 cases of 7 MG positive samples. No bacterial agent grew in 9 of the MG and MS positive cases. Compared to the results of histopathological findings where MS and MG antigens were detected, it was found that all of the cases had penuomonia that were in catarrhal or catarrhal hemorrhagic nature. As a result, in this study made retrospectively, the researchers suggest that MS and MG are the causative agent of the pneumonia, primarily or mix in the 18 chickens of 27 5 pneumonic broiler chicken lungs by immunohistochemical method. © Medwell Journals, 2011.
Keywords: Agent; Broiler chicken; Immunohistochemistry; Lungs; Mycoplasma gallisepticum; Mycoplasma synoviae; Pneumonia; Turkey